2011
DOI: 10.1007/s00421-011-2212-9
|View full text |Cite
|
Sign up to set email alerts
|

The physiological effects of low-intensity neuromuscular electrical stimulation (NMES) on short-term recovery from supra-maximal exercise bouts in male triathletes

Abstract: This study investigated the acute effects of NMES on blood lactate (BLa) and performance parameters in trained male triathletes. On three separate days, 13 trained male triathletes performed six 30 s Wingate tests (30 WanT) on a cycle ergometer. Each session consisted of performing 3 × 30 WanT (bouts 1-3) followed by a randomly assigned 30 min recovery intervention of either: (i) passive (seated), (ii) active (cycling at 30% VO(2 max)) or (iii) NMES (1 Hz/500 μs-ON:OFF 2:6 s). The 3 × 30 WanT bouts were then r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…In one hand, we suggest that the first exercise session, corresponding to a very exhaustive exercise, could have induced an important cardiac demand, needing a long recovery period to return to baseline. Indeed, Malone, et al 8 in their study have realized the exact same exercise-induced fatigue protocol (3 x 30 WAnT). They found similar results regarding heart rate during a 30 min recovery period of passive or NMES induced-blood flow recovery intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one hand, we suggest that the first exercise session, corresponding to a very exhaustive exercise, could have induced an important cardiac demand, needing a long recovery period to return to baseline. Indeed, Malone, et al 8 in their study have realized the exact same exercise-induced fatigue protocol (3 x 30 WAnT). They found similar results regarding heart rate during a 30 min recovery period of passive or NMES induced-blood flow recovery intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently proposed mechanism through which strategies may contribute to recovery after high-intensity exercise is by increasing or maintaining local and/or systemic blood flow [4][5][6][7][8] . Effective recovery strategies enhance blood flow to the recovering muscles, which is assumed to improve oxygen and nutrient delivery, and therefore PCr and glycogen resynthesis 9 , while at the same time transporting lactate and metabolic by-products such as H + ions, Pi, Mg 2+ , and NH3 away from the active muscles to removal sites and non-exercised muscles 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The unit was set to an established recovery mode, while the participants were asked to increase the stimulation intensity to the highest possible level without undue discomfort. The research team observed the participants during stimulation to assist with proper intensity of stimulation while also recording the stimulation setting as previously noted [23]. The treatment protocol consisted of nine sequences, with the first three stages lasting for two minutes and the remaining six for three minutes.…”
Section: Methodsmentioning
confidence: 99%
“…The results of this study showed a moderate recovery effect on lactate concentration after water rescue for the ES group compared with a PR group. These results are difficult to place in perspective with regard to the literature, because on the one hand no previous studies have used ES in lifesavers, and on the other hand, ES efficacy on blood lactate concentrations may be related to ES parameters used (pulse duration, current frequency, amplitude, and electrode placement) [9,32], target population [33], and type of fatiguing exercise or duration of recovery [32]. The present results are partially in agreement with a previous study in swimmers [8].…”
Section: Discussionmentioning
confidence: 99%